2019
DOI: 10.1007/s40801-019-00171-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Causal Analysis of the Effects of Long-Acting Muscarinic Antagonist Versus No Long-Acting Bronchodilator Use on Readmission or Mortality After Hospitalization for Chronic Obstructive Pulmonary Disease

Abstract: Background Retrospective observational studies may provide real-world evidence about long-acting muscarinic receptor antagonist (LAMA) effectiveness in reducing mortality or COPD-related readmission risk after a COPD hospitalization. Causal inference and competing risk statistical procedures aid in managing confounding and competing outcome events that complicate retrospective analyses. Objective To compare COPD-related readmission and mortality risk among patients receiving a LAMA versus patients receiving no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…The use of breathing treatments such as arformoterol was consistently associated with lower COPD readmission risk (53), even when compared to nebulized short-acting beta antagonists (SABA) (50). Moreover, the use of longacting muscarinic receptor antagonist (LAMA) therapy was also consistently associated with lower risk of readmission (32,52). Conversely, the use of steroids was more mixed within the literature with inhaled steroids (51) and systemic corticosteroids (31) being associated with lower readmission risk and bronchodilator corticosteroids being associated with higher readmission risk (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of breathing treatments such as arformoterol was consistently associated with lower COPD readmission risk (53), even when compared to nebulized short-acting beta antagonists (SABA) (50). Moreover, the use of longacting muscarinic receptor antagonist (LAMA) therapy was also consistently associated with lower risk of readmission (32,52). Conversely, the use of steroids was more mixed within the literature with inhaled steroids (51) and systemic corticosteroids (31) being associated with lower readmission risk and bronchodilator corticosteroids being associated with higher readmission risk (27).…”
Section: Discussionmentioning
confidence: 99%
“…Three 2010-2014 studies identified medication or vaccines increasing the risk of readmission (27,31,32), while two other studies identified statin prescriptions and arformoterol breathing treatments as decreasing the risk of readmission (32,50). Similarly, four studies from 2015-2020 time period identified a variety of medications as risk factors that increased the risk of readmission (34,42,49,51), while other medications were associated with a decreased risk of readmission (49,(51)(52)(53)(54).…”
Section: Interpersonal-level Risk Factorsmentioning
confidence: 99%